Assessment of the impact of DIAM interspinal dynamic stabilization on pain in the lumbar spine - the role of physiotherapy - Suszyński, Krzysztof; Dolińska, Anna; Górka, Dariusz (Journal of Education, Health and Sport, 2023)
Pain in the LS segment occurs in both young and old people. Stabilization training is gaining more and more supporters in returning to proper functioning. Central stabilization is the ability to maintain the correct body posture during static and dynamic movements. The DIAM system of dynamic interspinal stabilization of the spine is a minimally invasive procedure which, by inserting a silicone implant between the spinous processes, relieves the intervertebral joints, the intervertebral disc and reduces the pressure on the nerve structures. Continuation after the procedure is systematic physiotherapy. The aim of the study was to assess the impact of the implant and individually adjusted stabilization training of the lumbar-pelvic-hip complex in patients after dynamic interspinal stabilization with the DIAM method. The study was conducted on a group of 56 people who underwent a minimally invasive procedure and qualified from the 10th day after the operation. The stabilization training was selected individually for each patient, including the current state of health. The training was conducted once a week for four weeks. The conducted stabilization training of the lumbar-pelvic-hip complex turned out to be an effective method in recovery. There was a significant decrease in pain in the lower part of the spine among the examined patients. There was an improvement in physical activity and activities of daily living based on the Ronald-Morris scale. A decrease in the number of points was noted in all subjects. Fast, post-surgical rehabilitation therapy after using dynamic stabilization - DIAM, turned out to be a helpful method in faster recovery. It is reasonable to introduce early rehabilitation according to the scheme established by us after the DIAM dynamic stabilization procedure, as the period of return to work is reduced.